2019
DOI: 10.1002/chir.23078
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective ene‐reduction of E‐2‐cyano‐3‐(furan‐2‐yl) acrylamide by marine and terrestrial fungi and absolute configuration of (R)‐2‐cyano‐3‐(furan‐2‐yl) propanamide determined by calculations of electronic circular dichroism (ECD) spectra

Abstract: This work reports the green organic chemistry synthesis of E‐2‐cyano‐3(furan‐2‐yl) acrylamide under microwave radiation (55 W), as well as the use of filamentous marine and terrestrial‐derived fungi, in the first ene‐reduction of 2‐cyano‐3‐(furan‐2‐yl) acrylamide to (R)‐2‐cyano‐3‐(furan‐2‐yl)propanamide. The fungal strains screened included Penicillium citrinum CBMAI 1186, Trichoderma sp. CBMAI 932 and Aspergillus sydowii CBMAI 935, and the filamentous terrestrial fungi Aspergillus sp. FPZSP 146 and Aspergillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…ROA is advantageous because a wide range of molecules can be used as VCD, as it also observes vibrations and is sensitive to the chirality of the structure. Occurs in two different behaviors, the first aspect is incident circular polarization (ICP), where the light is circularly polarized in both directions, left or right, and the second is scattered circular polarization (SCP), where an incident light of fixed polarization is used to measuring the intensity of a circularly polarized component of scattered light [18].…”
Section: Raman Optical Activitymentioning
confidence: 99%
“…ROA is advantageous because a wide range of molecules can be used as VCD, as it also observes vibrations and is sensitive to the chirality of the structure. Occurs in two different behaviors, the first aspect is incident circular polarization (ICP), where the light is circularly polarized in both directions, left or right, and the second is scattered circular polarization (SCP), where an incident light of fixed polarization is used to measuring the intensity of a circularly polarized component of scattered light [18].…”
Section: Raman Optical Activitymentioning
confidence: 99%
“…Zhou et al reported that A. sydowii PT-2 isolated from Pu-erh tea degraded theobromine to 3-methylxanthine in a liquid culture through N-7 demethylation [ 124 ]. Also, Jimenez et al reported that A. sydowii CBMAI 935 associated with C. erecta sponge collected from Sao Sebastiao, São Paulo, Brazil, enantioselectively reduced ene of E-2-cyano-3-(furan-2-yl)acrylamide to (R)-2-cyano-3-(furan-2-yl)propanamide with a high yield [ 125 ]. In 2018, Morais et al studied the reduction of α-chloroacetophenones to (S)-alcohols using whole cells of marine-derived A. sydowii CBMAI 935 [ 126 ].…”
Section: Industrial and Biotechnological Applicationsmentioning
confidence: 99%
“…Mucor circinelloides , Mucor plumbeus , and Gliomastix masseei were the most versatile strains, showing the highest conversions for all the analyzed substrates. Avoiding an extensive review here, several other works showed the chemoselective reduction of α,β-unsaturated compounds using marine-derived fungi [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%